The Effect of Garam Masala Levels Addition on Chocolate Based Functional Beverage - Ratih Hardiyanti; Anjar Ruspita Sari (Journal of Applied Food Technology, 2020)
The increasing popularity of cocoa-based beverage has encouraged the development of various chocolate beverage formulations. Chocolate beverage formulations with addition of garam masala were carried out to produce functional beverage products which are beneficial to consumers and the product itself. Five different concentration of garam masala (0.01%, 0.02%, 0.03%, 0.04%, and 0.05%) were added into chocolate beverage. Preference test was carried out to evaluate panelists’ preference to each formula. Sensory evaluation was performed by giving an assessment using 7-scaled Likert scale for color, aroma, taste, warm sensation (after taste), and overall product. The results showed that the concentration of garam masala addition has an effect (p≤0.10) on the attributes of aroma, warm sensation, and overall product. The most preferred chocolate beverage was with the addition of 0.03% garam masala. Higher concentration of garam masala in chocolate based beverage resulted a higher antioxidant activity as well as phenolic content, as antioxidant component.